Physical characteristics and physiological attributes of female volleyball players - The need for individual data - Nikolaidis, P. T.; Ziv, G.; Veniamakis, E. E.; Arnon, M.; Lidor, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The purpose of this study was twofold: (a) to profile physical characteristics and physiological attributes of adolescent and adult Greek female volleyball players (n=61) who were members of the A (the best league for female volleyball players) and B (the second- best league for female volleyball players) Series clubs in Greece, and (b) to examine the intra-individual variability among these players in all physical and physiological measurements that were undertaken in the study. Methods: The participants were divided into three age groups - under 14, 14-18, and over 18 years. They underwent a series of physical (e.g., height, body mass, and percentage of body fat) and physiological (e.g., aerobic profile, flexibility, and vertical jumping ability) tests. Results: Three main findings emerged from the data analysis: (a) differences in physical characteristics and physiological attributes existed between the three age groups. For example, fat free mass was lower in players under the age of 14 (41.6+/-6.1 kg) compared to players between the ages of 14-18 (50.2+/-7.0 kg) and players over the age of 18 (52.0+/-3.4 kg). In addition, the relative peak power as measured in the WAnT was the highest in the over- 18 group (9.72+/-.65 W/kg), lower in the 14-18 group (8.95+/-.77), and the lowest in the under-14 group (8.32+/-.78 W/kg), (b) large intra-individual variability existed in most physical characteristics and physiological attributes measured in the study, and (c) the intraindividual variability was observed in all three groups. Conclusions: These findings emphasize the need for coaches to examine the intraindividual variability within the players on their teams, and to use this information when designing training programs and strength and conditioning programs.